Pengaruh Harga CPO, Biaya Lingkungan, dan Inventory turnover terhadap Profitabilitas Perusahaan Sawit - Mishel Mishel; Hana Dhayan; Elok Heniwati (Forum Kerjasama Pendidikan Tinggi, 2026)
This research analyze the of CPO prices, environmental costs (proxied by CSR/TJSL costs), and inventory turnover on profitability (Return on Assets/ROA) of 15 oil palm companies listed on the Indonesia Stock Exchange for the 2020–2024 period. Employing a quantitative approach with panel data (75 observations), the data were analyzed using the Random Effect Model in EViews 12. The results show that CPO prices have a positive and significant effect on ROA (coefficient = 0.1264; p = 0.0000), as do environmental costs (coefficient = 0.0145; p = 0.0117). Conversely, inventory turnover has a positive but non-significant effect (coefficient = 0.0028; p = 0.8816). Simultaneously, all three variables significantly affect profitability (p = 0.0000; R^2 = 37.56%). This study contributes by integrating external (CPO prices) and internal factors (CSR/TJSL and inventory turnover). The findings show that CPO prices and CSR/TJSL expenditures increase profitability, while inventory turnover does not directly determine ROA.